THE CHARACTER OF THE DISEASES’ CONSEQUENCES IN DISABLED CHILDREN WITH CIRCULATION ORGANS DISORDERS AND RHEUMATOID ARTHRITIS - Tolmachova, S.R.; Kolomiets, A.M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The data concerning the consequences of diseases in 110 disabled children with different pathologies of blood circulatory organs and in 115 disabled children with rheumatoid arthritis, are presented. It has been established that the leading disturbances are visceral, metabolic, motoric and psychological disturbances. The limitation of life functions is characterized by the decrease in motoric ability, in hand motion and body motorics during the solution of everyday life tasks. Their social deficience is connected with a limitation of physical independence, mobility and capacity of receiving education. A disadaptation to inner and outer world has been verified in 37,6 % of cases. The approaches to carrying out reabilitation measures at different levels of disease consequences are given.